Investor-State Dispute Settlement in the Context of the Implementation of New Generation Free trade Agreements and the Challenges for Vietnam - Thanh Thuy, Phan Thi (VNU Journal of Science: Legal Studies; Vol 38 No 4DO - 10.25073/2588-1167/vnuls.4514, 2022)
The requirement to settle international investment disputes arising from the new generation free trade agreements that Vietnam is a member of has been causing great pressure on the Vietnamese Government, authorities, and the system of national jurisdictions. This article will focus on analyzing and clarifying the main mechanisms of investor-state dispute settlement (ISDS) that have been applied in these free trade agreements and the legal and practical challenges the Government has been facing. As a result of the research findings, the article will make suggestions on solutions to improve the law and the institutions involved in ISDS in Vietnam.